2018
DOI: 10.3389/fcell.2018.00124
|View full text |Cite
|
Sign up to set email alerts
|

Bloody Zebrafish: Novel Methods in Normal and Malignant Hematopoiesis

Abstract: Hematopoiesis is an optimal system for studying stem cell maintenance and lineage differentiation under physiological and pathological conditions. In vertebrate organisms, billions of differentiated hematopoietic cells need to be continuously produced to replenish the blood cell pool. Disruptions in this process have immediate consequences for oxygen transport, responses against pathogens, maintenance of hemostasis and vascular integrity. Zebrafish is a widely used and well-established model for studying the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 127 publications
0
11
1
Order By: Relevance
“…Recently, it was reported that DDX41 regulates homeostasis by suppressing the cGAS-STING inflammatory pathway in zebrafish and human HSPCs, which is the opposite of what we observed here (18,19). Although HSC self-renewal and differentiation is highly conserved among vertebrates, zebrafish and mouse have different hematopoiesis timelines and erythropoiesis occurs at distinct sites (36)(37)(38). Thus, it is possible that DDX41 functions distinctly in different species.…”
Section: Discussioncontrasting
confidence: 76%
“…Recently, it was reported that DDX41 regulates homeostasis by suppressing the cGAS-STING inflammatory pathway in zebrafish and human HSPCs, which is the opposite of what we observed here (18,19). Although HSC self-renewal and differentiation is highly conserved among vertebrates, zebrafish and mouse have different hematopoiesis timelines and erythropoiesis occurs at distinct sites (36)(37)(38). Thus, it is possible that DDX41 functions distinctly in different species.…”
Section: Discussioncontrasting
confidence: 76%
“…The consumption of Western-type diets trigger myelopoiesis and transcriptional reprogramming of myeloid precursor cells 27 . Next, we decided to address if the increased number of neutrophils and macrophages found in NASH larvae were associated with increased proliferation at the caudal hematopoietic tissue (CHT) and the kidney, the hematopoietic niches where myelopoiesis occurs at this developmental stage 28 . To do so we incubated zebrafish larvae with EDU and measured the number of cells proliferating in the CHT, kidney, and thymus (Fig.…”
Section: Proliferation Of Multipotent Progenitors Is Enhanced In Nashmentioning
confidence: 99%
“…NS knock-in mice with activating PTPN11 mutations develop mild MPN only after 5 months of age (Araki et al, 2004(Araki et al, , 2009. Zebrafish (Danio rerio) with rapid ex-utero development, transparent embryos and conserved blood ontogeny emerged as a unique pediatric leukemia model that enables monitoring of leukemogenesis from its initial stages with high temporal and spatial resolution (de Pater & Trompouki, 2018;Gore et al, 2018). Furthermore, NSassociated features, such as shorter body axis length, craniofacial defects, defective gastrulation and impaired heart looping, are recapitulated in zebrafish embryos upon transient over-expression of NS-associated protein variants (Bonetti et al, 2014;Jopling et al, 2007;Niihori et al, 2019;Paardekooper Overman et al, 2014;Runtuwene et al, 2011).…”
Section: Introductionmentioning
confidence: 99%